Hidroformilação de álcoois biorrenováveis catalisada por complexo de ródio - Fábio Godoy Delolo (2018)
The rhodium complex catalysed hydroformylation of (1R)-(-)myrtenol and (1R)-(-)nopol, allylic and homoallylic biomass-based hydroxyolefins, containing trisubstituted endocyclic carbon-carbon double bond was studied systematically. Both substrates presented diastereofacial selectivity, being the major products of the respective substrates, formed through the interaction of the catalyst with the substrates by the less hindered face. Only the aldehyde derived from myrtenol undergoes an intramolecular hemiacetalization during the separation process. The cyclic product shows an unexpected structure due to the epimerization process The effects of the temperature, pressure, nature of phosphorus ligands, P/Rh molar ratio and solvent were studied aiming to develop a stable, active and selective catalytic system. The phosphorus auxiliary ligands evaluated were: PPh3, P(OPh)3 and tris(2,4-di-tert-butylphenyl)phosphite. The system was active only in presence of phosphites, with the P/Rh ratio being crucial for selectivity. The reactions can be also performed in eco-friendly: ethanol, 2-methyltetrahydrofuran, diethylcarbonate, and anisole as alternatives for rather toxic toluene.The processes developed in the present work represent a valuable route to novel fragrance aldehydes starting from bio-mass based substrates.